Reentrant albedo proton fluxes measured by the PAMELA experiment. Issue 5 (26th May 2015) - Adriani, O.; Barbarino, G. C.; Bazilevskaya, G. A.; Bellotti, R.; Boezio, M.; Bogomolov, E. A.; Bongi, M.; Bonvicini, V.; Bottai, S.; Bruno, A.; Cafagna, F.; Campana, D.; et al.
Abstract We present a precise measurement of downward going albedo proton fluxes for kinetic energy above ∼70 MeV performed by the Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics (PAMELA) experiment at an altitude between 350 and 610 km. On the basis of a trajectory tracing simulation, the analyzed protons were classified into quasi‐trapped, concentrating in the magnetic equatorial region, and untrapped spreading over all latitudes, including both short‐lived (precipitating) and long‐lived (pseudotrapped) components. In addition, features of the penumbra region around the geomagnetic cutoff were investigated in detail. PAMELA results significantly improve the characterization of the high‐energy albedo proton populations at low‐Earth orbits.